Implementation of COBIT 5 in Security, Risk, and Information Management at RRI Banjarmasin - Fatimah, Fatimah; Maria Peronika; Marliana (LPPM Universitas Sari Mulia, 2025)
This study aims to instill the maturity level of information technology governance at RRI Banjarmasin using the COBIT 5 framework, focusing on two domains, namely EDM03 (Ensure Risk Optimization) and APO13 (Manage Security). This second domain was chosen because it is directly related to risk management and information security of Publishing. The research method used is a qualitative approach through interviews and documentation analysis. The evaluation results show that the current maturity level value for EDM03 is 3.5 and APO13 is 3.6, which is at level 4 (Predictable) after rounding. Although the process has been running consistently, there is still an average gap of 1.45 towards level 5 (Optimizing). This finding indicates the need for continuous improvement so that IT governance at RRI Banjarmasin can achieve optimal conditions and support the quality of safe and reliable broadcasting services.